Prevalence of knee osteoarthritis among elderly persons in India: A systematic review and meta-analysis - Roy Arokiam Daniel; Mani Kalaivani; Praveen Aggarwal; Sanjeev Kumar Gupta (Journal of Family Medicine and Primary Care)
Background: Osteoarthritis (OA) is the most common cause of joint pain among the elderly population. It deteriorates their quality of life and poses economic burden to the family and the nation. Furthermore with increasing life expectancy and growing elderly population, the prevalence of OA will eventually increase. There is lack of national-level estimate on the prevalence of OA knee in India. Hence, this systematic review and meta-analysis were conducted to estimate the prevalence of OA knee among elderly persons in India. Methods: A systematic electronic search was conducted in PubMed, Embase, Cochrane Library, and Google Scholar to retrieve community-based studies which reported the prevalence of OA knee among elderly persons in India. To estimate the pooled prevalence and heterogeneity, the random effects model and I2 statistic methods were employed. We conducted subgroup analyses based on gender and study setting, criteria, and sensitivity analysis. Results: We included 14 studies in this meta-analysis, which comprised a total of 5,029 participants. The pooled prevalence of OA knee among elderly persons in India was 47% (95% CI: 38.4% to 55.8%, I2-97.1%) The subgroup analysis based on gender, criteria used, and study setting did not reveal the cause of heterogeneity. Sensitivity analysis after removing two studies did not change the pooled estimate. Conclusions: Almost half the elderly persons in India suffer from OA knee, posing a severe threat to the healthcare system. Hence, the strengthening of primary health care and increased rehabilitation services is needed to reduce the consequences of OA among elderly people.